ChemInform Abstract: Synthesis of Monosubstituted Thioureas by Vapour Digestion and Mechanochemical Amination of Thiocarbamoyl Benzotriazoles. Issue 38 (September 2016) - Dud, Mateja; Magdysyuk, Oxana V.; Margetic, Davor; Strukil, Vjekoslav
Abstract: Highly deactivated anilines, such as 4‐nitro and 4‐cyano are not applicable as substrates.